Evaluation of Three Human Cervical Fusion Implants for Use in the Canine Cervical Vertebral Column. Issue 7 (6th September 2016) - Morrison, Emily J.; Litsky, Alan S.; Allen, Matthew J.; Fosgate, Geoffrey T.; Hettlich, Bianca F.
Abstract : Objective: To assess technical feasibility and mechanical properties of 3 locking plate designs (Zero‐P, Zero‐P VA, and Uniplate 2) for use in the canine cervical spine. Study Design: Prospective ex vivo study. Animals: Cadaver cervical spines from skeletally mature large breed dogs (n = 18). Methods: Specimens were screened using radiography and allocated into balanced groups based on bone density. Stiffness of intact C4–C5 vertebral motion units was measured in extension, flexion, and lateral bending using nondestructive 4‐point bend testing. Uniplate 2 was then implanted at C4–C5 and mechanical testing was repeated. Mechanical test data were compared against those from 6 spines implanted with monocortical screws, an allograft ring spacer, and PMMA. Results: The Zero‐P and Zero‐P VA systems could not be surgically implanted due to anatomical constraints in the vertebral column sizes of the canine cervical spines used in this study. Fixation with Uniplate 2 or with screws/PMMA significantly increased stiffness of the C4–C5 vertebral motion units compared to unaltered specimens ( P  < .001) in extension. Stiffness of the titanium screw/PMMA fixation was significantly greater than the Uniplate 2 construct in extension. Flexion and lateral bending could not be evaluated in 3 of 6 specimens in the Uniplate 2 group due to failure at the bone/implant interface during extension testing. Conclusion: Fixation with Uniplate 2 was biomechanically inferior to screws/PMMA. Particularly concerning was the incidence of vertebral fracture after several testing cycles. Based on our results, Zero‐P, Zero‐P VA, and Uniplate 2 cannot be recommended for use in dogs requiring cervical fusion.